Modulation of human osteoclastogenesis and osteoblastogenesis by lycopene - Costa-Rodrigues, Joao (2022)
Lycopene is a lipid-soluble pigment that is mainly found in tomato. It is the carotenoid that presents the highest antioxidant potential, and due to that, it has been implicated in a decrease of the risk of several oxidative-stress-related disorders, such as cancer, inflammatory diseases and osteoporosis. Nevertheless, at the present, there is no detailed information about how lycopene affects bone metabolism. The aim of the present work was to characterize the cellular and molecular effects of lycopene on human osteoclast and osteoblast differentiation and function. It was observed that lycopene, at levels found in plasma after the ingestion of lycopene-containing products, decreased osteoclast differentiation but did not affect cell density/survival; calcium-phosphate resorbing ability was also decreased. On the other hand, osteoblast proliferation (via a decrease on apoptosis) and differentiation were increased in the presence of lycopene. The observed effects in both cell types appeared to be related to significant changes in MEK signaling pathway, but also in protein kinase C pathway in osteoclasts and NFkB signaling in osteoblasts. In conclusion, lycopene appears to promote an anabolic state of bone metabolism, stimulating osteoblastogenesis and inhibiting osteoclastogenesis, which may contribute to the promotion of a proper health status of bone tissue. This information might be relevant for the prevention and delay in the progression of osteolytic bone conditions.